Cow's Milk Allergy Prescribing Is Influenced by Regional and National Guidance. Issue 5 (May 2016) - Wauters, Lucas; Brown, Trevor; Venter, Carina; Dziubak, Robert; Meyer, Rosan; Brogan, Breege; Walsh, Joanne; Fox, Adam T.; Shah, Neil
ABSTRACT: Objectives: Cow's milk allergy (CMA) is the most common food allergy in children with many clinical manifestations, leading to misdiagnoses such as gastro-oesophageal reflux, infantile colic, and lactose intolerance with inappropriate prescribing. We aimed to determine the impact of infant feeding guidelines on CMA prescribing in UK primary care using a simple and inexpensive training package. Methods: Prospectively collected data of infant feeding prescriptions in Northern Ireland from June 2012 to March 2014 were analysed with the intervention period between November 2012 and March 2013. A comparison was made between hypoallergenic formulae, appropriate for CMA, versus alternative prescriptions including antiregurgitation and colic products, lactose-free and partially hydrolysed milks, or infant Gaviscon. Results: Comparing pre- and postintervention period, the total quantity of hypoallergenic formulae increased by 63.2% and alternative prescriptions decreased by 44.6% ( P  < 0.001). The total amount of all prescribed products decreased by 41.0% ( P  < 0.001). During the study period, the proportion of recommended CMA treatment increased from 3.4% before training to 9.8% in the short- and long-term follow-up ( P  < 0.001). The overall increase was £33, 508 per year or £95.5 per general practitioner's surgery. Conclusions: We present the first study evaluating the impact of infant feeding guidelines on CMA prescribing in UK primary care. Practical advice and teaching of health professionals allowed for effective implementation of regional and national guidelines, with a significant impact on prescription patterns. This study shows promising results for prospective research on a national scale, including socioeconomical impact and cost-effectiveness.